Efeitos do exercício intervalado na expressão de proteínas inflamatórias e catabólicas na musculatura esquelética de ratos tratados com dexametasona - Martuscelli, Aline Mio (Universidade Federal de São Carlos, 2014)
Dexamethasone is widely used in clinical use due to its potent anti-allergic and antiinflammatory effects, but it has been shown that its chronic use can induce several side effects such as hyperglycemia, hypertension, hypercholesterolemia and muscle atrophy. Muscle atrophy occurs by an imbalance between catabolic and anabolic protein levels. Among catabolic proteins, FOXO3a, MuRF-1 and Atrogin-1 are directly related to muscle atrophy induced by dexamethasone. Furthermore, it is known that some inflammatory proteins (TNF-α and IL-6) also participate in reduction of muscle weight. We have shown that aerobic exercise attenuates some of the side effects of dexamethasone, but nothing is known about interval training (IT) performed before and concomitant dexamethasone treatment. This study investigated if interval training is effective in attenuating muscle atrophy induced by dexamethasone and if the proteins FOXO3a, MuRF-1, Atrogina-1, TNF-αand IL-6 are involved in this response. Rats were distributed into 4 groups: sedentary control (SC), sedentary + Dexa (SD), trained control (TC), and trained + Dexa (TD), and underwent an interval training period (50% and 80% of maximal capacity, 2 and 1 min, respectively, 1h/day, 5 days / week, 70 days) or remained sedentary. Dexamethasone was administered during the last 10 days (0.5mg/kg per day i.p.). The rats were weighed weekly during training and daily during the treatment. The tibialis anterior (TA), soleus (SOL) and flexor hallucis longus (FHL) were collected, weighed and stored for analysis of TNF-α, IL-6, FOXO3a, MuRF-1 and Atrogin-1protein levels using electrophoresis method, Western Blotting. Administration of dexamethasone resulted in a significant decrease in body weight (-17%) followed by reduction in TA (-22%) and FHL (-19%) muscles weight. This reduction in muscle weight involved a significant increase in MuRF-1 protein levels in TA (+27%) and FHL (+18%) muscles, although TNF-α (-37%FHL and -15% SOL) and IL-6 (-26% TA, - 24% FHL and -18% SOL) protein levels were reduced. Interval training was effective in blocking the increase of MuRF-1protein level in TA and FHL muscles, moreover interval training significantly reduced FOXO3a production level in TA muscle, in both groups, TC (-27%) and TD (-32%).This response was followed by an attenuation of TA muscle mass after training. Chronic treatment with dexamethasone, as well as training, did not change Atrogin-1protein level. The results of the present study allow us to conclude that MuRF-1 seems to be involved in TA and FHL muscle atrophy induced by dexamethasone treatment, independent of inflammatory proteins signaling. On the other side, interval training determined TA muscle atrophy attenuation by decreasing MuRF-1 and FOXO3a without changes in TNF-α e IL-6 protein levels.
Keywords: Dexametasona; Treinamento intervalado; Atrofia muscular; Proteínas; Glicocorticoides; FOXO3a; MuRF-1, Atrogina-1; Interval training; Muscle atrophy; Glucocorticoids; CIENCIAS BIOLOGICAS::FISIOLOGIA